Articulated dissent and immediacy: a cross-national analysis of the effects of COVID-19 lockdowns. Issue 2 (20th September 2021) - Croucher, Stephen Michael; Kelly, Stephanie; Hui, Chen; Rocker, Kenneth J.; Cullinane, Joanna; Homsey, Dini; Ding, George Guoyu; Nguyen, Thao; Anderson, Kirsty Jane; Green, Malcolm; Ashwell, Doug; Wright, Malcolm; et al.
Abstract : Purpose: In the midst of the COVID-19 pandemic, this study aims to explore how working remotely might impact the superior–subordinate relationship. Specifically, this study examines how immediacy explains articulated dissent, considers how an individual's attitudes toward online communication predicts immediacy and articulated dissent and compares these relationships in England, Australia and the USA. Design/methodology/approach: Three nations were examined: Australia, England and the USA ( n = 1, 776). Surveys included demographic questions and the following measures: organizational dissent scale, perceived immediacy measure, computer-mediated immediate behaviors measure and measure of online communication attitude. Findings: The results reveal supervisors' computer-mediated immediate behaviors and perceived immediacy both positively predict dissent. Some aspects of online communication attitudes positively predict computer-mediated immediate behaviors and perceived immediacy. In addition, attitudes toward online communication positively predict dissent. National culture influences some of these relationships; in each case the effects were substantively larger for the USA when compared to the other nations. Originality/value: This study is the first to cross-culturally analyze dissent and immediacy. In addition, this study considers the extent to which the COVID-19 pandemic influences the superior–subordinate relationship.